Silane crosslinking low-smoke halogen-free polyolefin cable material and preparation method thereof
By adding ionic liquids to silane crosslinking low-smoke halogen-free polyolefin cable materials and adjusting the proportion of polyolefin resin, the problems of slow crosslinking reaction speed and unsatisfactory crosslinking degree of traditional cable materials are solved, and faster crosslinking speed and better cable material performance are achieved.
Patent Information
- Application Number
- CN202510294726.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional silane crosslinking low-smoke halogen-free polyolefin cable materials have slow crosslinking reaction speed in large-section cable materials, which affects production efficiency, and the crosslinking degree and uniformity are not ideal, affecting the final performance of the cable materials.
By adding ionic liquid to the cable material as a promoter, the ion concentration of the reaction system is increased and the reaction activity is improved, thereby accelerating the hydrolysis and condensation reaction of silanol and the crosslinking reaction of silane. At the same time, the proportion of polyolefin resin is adjusted and the amount of compatibility agent is increased to improve the dispersion of powder in the material.
The crosslinking speed and crosslinking effect are significantly improved, the overall performance and production efficiency of cable materials are improved, and the mechanical strength, thermal aging performance and flame retardancy of the material are ensured.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of cable materials, and more specifically, to a silane cross-linked low-smoke halogen-free polyolefin cable material and a preparation method thereof. Background Art
[0002] With the rapid development of the power and communication industries, the demand for cable materials is growing. Silane cross-linked low-smoke halogen-free polyolefin cable materials are widely used in cable manufacturing because of their excellent flame retardancy, chemical resistance and processing performance. The three-dimensional Si-O-Si structure formed after cross-linking can significantly improve the mechanical strength and service life of the material. The advantages of silane cross-linking are also wide processing temperature range, simple processing, convenient operation and low investment cost. However, the traditional silane cross-linking method still has some shortcomings. For example, for cable materials with large cross-sections, due to the large thickness of their insulation or sheath, the water penetration rate is slow, resulting in a relatively slow cross-linking reaction rate. It still takes a long time to complete the cross-linking reaction under the conditions of boiling or steam bath, which affects the production efficiency to a certain extent; and the degree of cross-linking and uniformity are sometimes not ideal, affecting the final properties of the cable material such as mechanical properties and aging properties.
[0003] Therefore, developing a silane-crosslinked low-smoke halogen-free polyolefin cable material that can effectively increase the crosslinking speed and have a better crosslinking effect is of great practical significance for improving the overall performance and production efficiency of the cable material. Summary of the invention
[0004] The present application provides a silane cross-linked low-smoke halogen-free polyolefin cable material and a preparation method thereof, which can effectively increase the cross-linking speed and achieve a better cross-linking effect, thereby improving the overall performance and production efficiency of the cable material.
[0005] The first aspect of the present application provides a silane cross-linked low-smoke halogen-free polyolefin cable material, wherein the raw materials for preparing the cable material include, by weight: 100 parts of polyolefin resin; 150-180 parts of hydroxide flame retardant; 5-10 parts of montmorillonite; 2 to 6 parts of vinyl trimethoxyethoxysilane; 2 to 6 parts of ionic liquid; Antioxidant 0-2 parts.
[0006] By adopting the above technical scheme, the ionic liquid in the silane cross-linked low-smoke halogen-free polyolefin cable material can be used as a promoter to increase the ion concentration of the reaction system and improve the reaction activity, thereby accelerating the hydrolysis and condensation reaction of silanol, completing the cross-linking reaction in a shorter time, accelerating the cross-linking reaction of silane and thus improving production efficiency; at the same time, the use of ionic liquids can also help improve the uniformity of the cross-linking reaction, making the performance of the cable material more stable and reliable.
[0007] Optionally, the polyolefin resin includes ethylene-vinyl acetate copolymer, ethylene-octene copolymer, polyethylene, and maleic anhydride grafted compatibilizer.
[0008] Optionally, the weight ratio of the ethylene-vinyl acetate copolymer, the ethylene-octene copolymer, the polyethylene, and the maleic anhydride grafted compatibilizer is (2-3): 1: 0.3: (0.3-0.6).
[0009] By adopting the above technical solution, adjusting the proportion of polyolefin resin and appropriately increasing the amount of compatibilizer, it is helpful to improve the dispersibility of powder in the material and help improve the flame retardancy of the material.
[0010] Optionally, the polyethylene is selected from one or more of high-density polyethylene and metallocene linear low-density polyethylene.
[0011] By adopting the above technical solution, the polyethylene does not contain low-density polyethylene, has a faster wire-paying speed, and a smoother wire surface, which helps to improve the processing performance of the material.
[0012] Optionally, the ionic liquid is selected from one or more of tetrafluoroborate and octamolybdate.
[0013] Further, the preparation steps of the tetrafluoroborate are as follows: Step 1: dissolving N-methylimidazole and ethyl bromoacetate in an organic solvent in a certain ratio, and then heating at 45°C to 80°C to react to obtain an intermediate product; Step 2: dissolving the intermediate product and NaBF4 in an organic solvent and stirring to react to obtain the tetrafluoroborate.
[0014] Further, the preparation steps of the octamolybdate are as follows: Step 1: dissolving N-methylimidazole and butyl bromide in an organic solvent in proportion, and then adding them to react to obtain an intermediate product; Step 2: The intermediate product and molybdate are mixed and dissolved and reacted at room temperature to obtain the octamerized molybdate.
[0015] Optionally, the antioxidant is selected from one or more of phenolic antioxidants, phosphite antioxidants, and thioester antioxidants.
[0016] Optionally, the hydroxide flame retardant is selected from one or more of aluminum hydroxide, magnesium hydroxide, iron hydroxide and boehmite.
[0017] The second aspect of the present application provides a method for preparing the silane cross-linked low-smoke halogen-free polyolefin cable material as described above, comprising the following steps: Step 1: polyolefin resin, hydroxide flame retardant, montmorillonite, and antioxidant are uniformly mixed, vinyl trimethoxyethoxysilane and ionic liquid are added, and mixing is continued to obtain a mixture; Step 2: sending the mixture into a screw extruder for extrusion and granulation to obtain the cable material.
[0018] By adopting the above technical solution, vinyltrimethoxyethoxysilane can react away trace amounts of water while undergoing a grafting reaction in a twin-screw extruder under the preparation method, thereby effectively reducing the risk of pre-crosslinking reactions of the material and enabling the product to have excellent process performance.
[0019] In summary, the present application includes at least one of the following beneficial technical effects: (1) The present application promotes the hydrolysis and condensation of silane by adding ionic liquid, so that the material has a faster reaction rate. At the same time, the product meets the high line speed requirements, has a moderate degree of crosslinking, and retains excellent mechanical and thermal aging properties; (2) By adding ionic liquid, the present application can improve the surface treatment effect of silane on magnesium hydroxide, aluminum hydroxide or montmorillonite, make the powder more evenly dispersed in the product, and improve the mechanical properties and flame retardancy of the product; (3) In the present invention, the vinyl trimethoxyethoxysilane not only acts as a coupling agent but also as a dehumidifier. It can react and remove trace amounts of water during the grafting reaction in a twin-screw extruder, effectively reducing the risk of pre-crosslinking reaction of the material and making the product have excellent processability. DETAILED DESCRIPTION
[0020] The present invention is described in detail below by way of examples. It is necessary to point out here that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by professionals and technicians in this field based on the content of the present invention above still belong to the scope of protection of the present invention.
[0021] Preparation Example 1 The preparation steps of ionic liquid E1 are as follows:
[0022] S1. Add 4 mL (0.05 mol) of N-methylimidazole and 12.5 mL of acetone to a 100 mL three-necked round-bottom flask and place the flask in a 60 °C constant temperature water bath. S2. Under nitrogen protection, slowly drop 6.2 mL (about 0.055 mol) of ethyl bromoacetate, heat under reflux for 6 h while stirring, and separate the liquid layers after the reaction. Separate the lower layer of liquid, wash it with petroleum ether for 4 times, distill off the solvents acetone and petroleum ether under reduced pressure, and then place it in a vacuum drying oven and dry it at 70 °C for 10 h to obtain a light yellow liquid intermediate 1.
[0023] S3. Add 1 g (5.0 mmol) of intermediate 1 to 2 mL of acetonitrile, add 0.54 g (5.0 mmol) of NaBF4 to the solution, stir at room temperature for 48 h to obtain a mixture of white solid and liquid, filter off the generated white solid, add 1 mL of chloroform to the filtrate, filter again, remove the chloroform, and obtain a light yellow viscous liquid; S4, washed with petroleum ether several times, then distilled under reduced pressure to remove petroleum ether and solvent acetonitrile, placed in a vacuum drying oven, and dried at 70 °C for more than 12 h to obtain a light yellow ionic liquid E1.
[0024] The structure of E1 was identified by H-NMR spectrum: 1 H NMR (400 MHz, CDCl3): 9.1 (s,1H), 7.7 (s, 2H), 5.3 (s, 2H), 4.2 (q, J =7.2 Hz, 2H), 3.9 (s,3H), 1.2 (t, J =7.2 Hz, 3H).
[0025] Preparation Example 2 The preparation steps of ionic liquid C2 are as follows:
[0026] S1. Add 4 mL (0.05 mol) of N-methylimidazole and 6.5 mL (0.06 mol) of butyl bromide into a 100 mL single-necked flask, take 15 mL of toluene as solvent, and then place in a 110 °C oil bath and stir under reflux for 18 h.
[0027] S2. After the reaction is completed, toluene is removed by distillation under reduced pressure to obtain a viscous yellow liquid, which is washed with ethyl acetate for multiple times. Finally, the product is dried in a vacuum drying oven at 70°C to obtain an intermediate product 2.
[0028] Example 1
[0029] A silane cross-linked low-smoke halogen-free polyolefin cable material, comprising the following components in parts by weight: 100 parts of polyolefin resin, 150 parts of hydroxide flame retardant, 5 parts of montmorillonite, 2 parts of vinyl trimethoxyethoxy silane, 12 parts of ionic liquid E, and 1 part of antioxidant; The polyolefin resin includes ethylene-vinyl acetate copolymer, ethylene-octene copolymer, metallocene linear low-density polyethylene, and maleic anhydride grafted compatibilizer, with a weight ratio of 2:1:0.3:0.3; the ethylene-vinyl acetate copolymer is purchased from EVA 40W of DuPont of the United States, the ethylene-octene copolymer is DF840 of Mitsui Chemicals, the metallocene linear low-density polyethylene is purchased from SP1520 of Evolue MLLDPE of Japan, and the maleic anhydride grafted compatibilizer is purchased from MC226 of Nengzhiguang; The hydroxide flame retardant is aluminum hydroxide; The montmorillonite was purchased from Zhejiang Fenghong New Materials Co., Ltd. SM001; The antioxidants are antioxidant 1790, antioxidant 168, pentaerythritol tetrakis (3-laurylthiopropionate), and dioctadecyl pentaerythritol diphosphite, and the weight ratio is 3:1:1:1.
[0030] A method for preparing the cable material as described above comprises the following steps: Step 1: After the polyolefin resin, the hydroxide flame retardant, the montmorillonite and the antioxidant were mixed at 40 rpm for 10 minutes, vinyl trimethoxyethoxysilane and the ionic liquid E1 were added, and the mixture was continued for 15 minutes to obtain a mixture 1; Step 2: feeding the mixture into a screw extruder for extrusion and granulation to obtain the cable material; the aspect ratio of the twin-screw extruder is 44:1; the temperatures of each section of the twin-screw extruder body are: 80°C-100°C, 125°C-130°C, 130°C-135°C, 135°C-140°C, 140°C-145°C, 145°C-150°C, 145°C-150°C, 145°C-150°C, 145°C-150°C, 145°C-150°C, 150°C-155°C; the head temperature of the twin-screw extruder is 145°C-150°C.
[0031] Example 2
[0032] A silane cross-linked low-smoke halogen-free polyolefin cable material, the formula components of which are substantially the same as those of Example 1, except that the ionic liquid E1 is present in 4 parts by weight.
[0033] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0034] Example 3
[0035] A silane cross-linked low-smoke halogen-free polyolefin cable material, the formula components of which are substantially the same as those of Example 1, except that the ionic liquid E1 is 6 parts by weight.
[0036] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0037] Example 4 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 1, except that the polyolefin resin includes ethylene-vinyl acetate copolymer, ethylene-octene copolymer, metallocene linear low-density polyethylene, and maleic anhydride grafted compatibilizer, and the weight ratio is 3:1:0.3:0.6.
[0038] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0039] Example 5 A silane cross-linked low-smoke halogen-free polyolefin cable material, comprising the following components in parts by weight: 100 parts of polyolefin resin, 180 parts of hydroxide flame retardant, 10 parts of montmorillonite, 4 parts of vinyl trimethoxyethoxy silane, 4 parts of ionic liquid E1, and 1 part of antioxidant; The polyolefin resin includes ethylene-vinyl acetate copolymer, ethylene-octene copolymer, polyethylene, and maleic anhydride grafted compatibilizer in a weight ratio of 3:1:0.3:0.6; the polyethylene includes high-density polyethylene and metallocene linear low-density polyethylene in a weight ratio of 1:1; the high-density polyethylene is purchased from ExxonMobil HTA108, and when mixed with metallocene linear low-density polyethylene, the processability of the material is improved; The hydroxide is a mixture of aluminum hydroxide and magnesium hydroxide in a weight ratio of 4:1; The antioxidants are antioxidant 1790, antioxidant 168, pentaerythritol tetrakis (3-laurylthiopropionate), and dioctadecyl pentaerythritol diphosphite, and the weight ratio is 3:1:1:1.
[0040] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0041] Example 6 A silane cross-linked low-smoke halogen-free polyolefin cable material, comprising the following components in parts by weight: 100 parts of polyolefin resin, 180 parts of hydroxide flame retardant, 10 parts of montmorillonite, 4 parts of vinyl trimethoxyethoxy silane, 4 parts of ionic liquid C2, and 1 part of antioxidant;
[0042] The polyolefin resin includes ethylene-vinyl acetate copolymer, ethylene-octene copolymer, polyethylene, and maleic anhydride grafted compatibilizer in a weight ratio of 3:1:0.3:0.6; the polyethylene includes high-density polyethylene and metallocene linear low-density polyethylene in a weight ratio of 1:1; the high-density polyethylene is purchased from ExxonMobil HTA108, and when mixed with metallocene linear low-density polyethylene, the processability of the material is improved;
[0043] The hydroxide is a mixture of aluminum hydroxide and magnesium hydroxide in a weight ratio of 4:1; The antioxidants are antioxidant 1790, antioxidant 168, pentaerythritol tetrakis (3-laurylthiopropionate), and dioctadecyl pentaerythritol diphosphite, and the weight ratio is 3:1:1:1.
[0044] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0045] Example 7 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 6, except that the ionic liquid C2 is 6 parts by weight.
[0046] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0047] Comparative Example 1 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 5, except that no ionic liquid E1 is added.
[0048] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0049] Comparative Example 2 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 5, except that the polyethylene includes high-density polyethylene and low-density polyethylene, and the weight ratio is 1:1.
[0050] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0051] Comparative Example 3 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 6, except that 2 parts of ionic liquid C2 are added.
[0052] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0053] Comparative Example 4 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 6, except that the accelerator is bismuth isooctanoate.
[0054] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0055] Comparative Example 5 A silane cross-linked low-smoke halogen-free polyolefin cable material, whose formula components are basically the same as those of Example 6, except that the accelerator is 4-dimethylaminopyridine.
[0056] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0057] Comparative Example 6 A silane cross-linked low-smoke halogen-free polyolefin cable material, the formula components of which are substantially the same as those of Example 1, except that: 120 parts of hydroxide flame retardant.
[0058] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0059] Comparative Example 7 A silane cross-linked low-smoke halogen-free polyolefin cable material, the formula components of which are basically the same as those of Example 1, except that 3 parts of montmorillonite are included.
[0060] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0061] Comparative Example 8 A silane cross-linked low-smoke halogen-free polyolefin cable material, the formula components of which are substantially the same as those of Example 1, except that no vinyl trimethoxyethoxy silane is added.
[0062] A method for preparing the cable material as described above is exactly the same as that in Example 1.
[0063] Performance Evaluation The silane cross-linked low-smoke halogen-free polyolefin cable material provided in the embodiments and comparative examples is prepared by molding or other suitable methods. The tubular sample is cut and weighed, and preheated in a hydraulic press at 170℃-180℃ without pressure for 60s. Then it is pressurized for 4 minutes, and the pressure of the hydraulic press is greater than 15MPa. Cool to room temperature under pressure. The test piece should be flat and smooth, with uniform thickness and no bubbles. Then immerse the test piece in a water bath at a temperature of 90℃~95℃ for 0.5~4 hours. The test piece should still remain flat after warm water cross-linking. The performance characterization test results are shown in Tables 1 and 2.
[0064] Table 1
[0065]
[0066] Table 2
[0067] Analysis of results in Table 1 and Table 2: From Example 1 and Comparative Examples 6-7, it can be seen that the silane cross-linked low-smoke halogen-free polyolefin cable material prepared by the present invention has excellent mechanical properties when a small amount of hydroxide is added or a small amount of montmorillonite is added, but its flame retardancy is poor and it is difficult to meet the safety requirements for use; From Example 1 and Comparative Example 8, it can be seen that Example 1 increases the amount of vinyl trimethoxyethoxy silane used as a coupling agent relative to Comparative Example 8, thereby increasing the grafting rate of the material and improving the crosslinking speed. From Examples 1-3 and Comparative Example 1, it can be seen that by adding and appropriately increasing the amount of the ionic liquid accelerator E1, the crosslinking speed of the cable material is significantly improved, and the surface treatment effect of the silicone on aluminum hydroxide or montmorillonite can be improved, so that the powder is dispersed more evenly in the product, and the mechanical properties and flame retardancy of the product are improved. However, excessive addition causes the liquid additive to fill the molecular gap of the material, limiting the movement space of the molecular chain, making it difficult for the molecular chain to fully stretch and slip when stretched, thereby reducing the elongation of the material; It can be seen from Examples 1 and 4 that adjusting the ratio of the resin and appropriately increasing the amount of the compatibilizer can help improve the dispersibility of the powder in the material and help improve the flame retardancy of the material; From Examples 4-5, it can be seen that the flame retardancy of the composite flame retardant of magnesium hydroxide and aluminum hydroxide is better than that of a single aluminum hydroxide flame retardant. At the same time, when high-density polyethylene ExxonMobil HTA108 is mixed with metallocene linear low-density polyethylene, the processability of the material is improved, so that the extruded sample has a very smooth surface and resistance to melt fracture. From Examples 6-7 and Comparative Example 3, it can be seen that by adding and appropriately increasing the amount of ionic liquid accelerator C2, the crosslinking speed of the cable material is significantly improved. Like E1, it can also improve the surface treatment effect of silicone on the powder, making the powder more evenly dispersed, which helps to improve the mechanical properties and flame retardancy of the product. Further increasing the addition amount does not significantly promote the crosslinking speed, but instead causes a waste of cost. Comparative Examples 4-5 are commonly used commercial rubber accelerators. It can be seen that their efficiency in promoting silane cross-linking is significantly lower than that of the ionic liquid accelerators E1 and C2 prepared in Preparation Examples 1 and 2.
[0068] Example 5 and Comparative Example 2 were also tested for pay-off speed, where the pay-off speed was the length of the sample extruded per minute by the SJ-70 extruder. Results: The pay-off speed of Example 8 was 120 m / min, while the pay-off speed of Comparative Example 2 was only 70 m / min. Although there was no significant difference in the physical and chemical properties and cross-linking speed of the product, Example 8 was significantly better than Comparative Example 2 in terms of processability, having a faster pay-off speed and a smoother line surface.
[0069] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be conceived, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, it is the applicant's intention that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A silane cross-linked low-smoke halogen-free polyolefin cable material, characterized in that: The raw materials for preparing the cable material include, by weight: 100 parts of polyolefin resin; 150-180 parts of hydroxide flame retardant; 5-10 parts of montmorillonite; 2 to 6 parts of vinyl trimethoxyethoxysilane; 2 to 6 parts of ionic liquid; Antioxidant 0-2 parts.
2. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 1, characterized in that: The polyolefin resin includes ethylene-vinyl acetate copolymer, ethylene-octene copolymer, polyethylene, and maleic anhydride grafted compatibilizer.
3. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 2, characterized in that: The weight ratio of the ethylene-vinyl acetate copolymer, the ethylene-octene copolymer, the polyethylene and the maleic anhydride grafted compatibilizer is (2-3):1:0.3:(0.3-0.6).
4. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 3, characterized in that: The polyethylene is selected from one or more of high-density polyethylene and metallocene linear low-density polyethylene.
5. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 1, characterized in that: The ionic liquid is selected from one or more of tetrafluoroborate and octamolybdate.
6. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 5, characterized in that: The preparation steps of the tetrafluoroborate are as follows: Step 1: dissolving N-methylimidazole and ethyl bromoacetate in an organic solvent in a certain ratio, and then heating at 45°C to 80°C to react to obtain an intermediate product; Step 2: dissolving the intermediate product and NaBF4 in an organic solvent and stirring to react to obtain the tetrafluoroborate.
7. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 5, characterized in that: The preparation steps of the octamolybdate are as follows: Step 1: dissolving N-methylimidazole and butyl bromide in an organic solvent in proportion, and then adding them to react to obtain an intermediate product; Step 2: The intermediate product and molybdate are mixed and dissolved and reacted at room temperature to obtain the octamerized molybdate.
8. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 1, characterized in that: The antioxidant is selected from one or more of phenolic antioxidants, phosphite antioxidants, and thioester antioxidants.
9. The silane cross-linked low-smoke halogen-free polyolefin cable material according to claim 1, characterized in that: The hydroxide flame retardant is selected from one or more of aluminum hydroxide, magnesium hydroxide, iron hydroxide and boehmite.
10. A method for preparing a silane cross-linked low-smoke halogen-free polyolefin cable material according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: polyolefin resin, hydroxide flame retardant, montmorillonite, and antioxidant are uniformly mixed, vinyl trimethoxyethoxysilane and ionic liquid are added, and mixing is continued to obtain a mixture; Step 2: sending the mixture into a screw extruder for extrusion and granulation to obtain the cable material.
Citation Information
Patent Citations
Flame-retardant rigid polyurethane foam prepared by taking ionic liquid as flame retardant agent
CN102329408A
Natural silane cross-linking LSOH (Low Smoke Zero Halogen) flame-retardant polyolefin cable material and preparation method thereof
CN103013020A
Silane crosslinked low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof
CN114015147A
Polyolefin composition as well as preparation method and application thereof
CN115368669A